Human-Nature Relationship in Heathy Landscape with Dormouse: Greg Gerrard's Ecocritical Approach - Irma Rahmawati; Rochmah Rochmah (Dinasti Publisher, 2024)
This study seeks the intricate relationship between humans and nature in Sylvia Townsend Warner's short story